2001
DOI: 10.1186/1471-230x-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Do published guidelines for evaluation of Irritable Bowel Syndrome reflect practice?

Abstract: Background: The only US guidelines listed in the National Guideline Warehouse for the diagnosis of Irritable Bowel Syndrome (IBS) are the expert opinion guidelines published by The American Gastroenterology Association. Although the listed target audience of these guidelines includes family physicians and general internists, the care recommended in the guidelines has not been compared to actual primary care practice. This study was designed to compare expert opinion guidelines with the actual primary care prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
(14 reference statements)
0
21
0
1
Order By: Relevance
“…Most of the evidence relating to the importance of excluding alarm features must be inferred through indirect evidence from reports of longitudinal follow‐up of patients diagnosed with IBS who did not have alarm features. In one study, Yawn et al 41 reviewed the medical records of 149 patients diagnosed with IBS. During 3 years of follow‐up, one patient out of 149 (0.67%) was diagnosed with organic disease (IBD) felt to be responsible for their gastrointestinal symptoms.…”
Section: When Should Diagnostic Testing Be Considered?mentioning
confidence: 99%
“…Most of the evidence relating to the importance of excluding alarm features must be inferred through indirect evidence from reports of longitudinal follow‐up of patients diagnosed with IBS who did not have alarm features. In one study, Yawn et al 41 reviewed the medical records of 149 patients diagnosed with IBS. During 3 years of follow‐up, one patient out of 149 (0.67%) was diagnosed with organic disease (IBD) felt to be responsible for their gastrointestinal symptoms.…”
Section: When Should Diagnostic Testing Be Considered?mentioning
confidence: 99%
“…The final number of subjects was therefore 149. Data regarding the testing done at the time of the diagnosis have been published previously 5, 6 …”
Section: Data Collectionmentioning
confidence: 99%
“…The irritable bowel syndrome (IBS) is a clinical syndrome defined by a combination of abdominal pain associated with a change in bowel habit and features of disordered defecation, often with bloating, which is not explained by a structural or biochemical abnormality 1, 2 . IBS is a common condition 3, 4 resulting in multiple physician visits and substantial health care costs 5–8 . Still, only about 50% of people with IBS choose to seek care for their condition 3, 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter is not often the case, as was shown in a number of studies: Of all patients (n=148) who matched the primary care definition of IBS, only 62% and 18% fulfilled the Manning and Rome II criteria, respectively, according to a Dutch investigation [37]. A study by Yawn et al [38] showed that not one of 149 IBS patients was diagnosed according to the gastroenterological standards set by the respective professional society (USA: American Gastroenterology Association, American College of Gastroenterology) at their family physician, and especially the request for a (negative) colonoscopy was met in only 41% of cases.…”
Section: Psychosomatics/psychiatrymentioning
confidence: 89%